-5(x-6)=-34+3x

Simple and best practice solution for -5(x-6)=-34+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-6)=-34+3x equation:


Simplifying
-5(x + -6) = -34 + 3x

Reorder the terms:
-5(-6 + x) = -34 + 3x
(-6 * -5 + x * -5) = -34 + 3x
(30 + -5x) = -34 + 3x

Solving
30 + -5x = -34 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
30 + -5x + -3x = -34 + 3x + -3x

Combine like terms: -5x + -3x = -8x
30 + -8x = -34 + 3x + -3x

Combine like terms: 3x + -3x = 0
30 + -8x = -34 + 0
30 + -8x = -34

Add '-30' to each side of the equation.
30 + -30 + -8x = -34 + -30

Combine like terms: 30 + -30 = 0
0 + -8x = -34 + -30
-8x = -34 + -30

Combine like terms: -34 + -30 = -64
-8x = -64

Divide each side by '-8'.
x = 8

Simplifying
x = 8

See similar equations:

| 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 | | 5n-n=15+7 | | 7x-x=-16-2x | | -7r-8-5r=-13-7r | | 9x+45=100 | | f(x)=(x^7-4x^6)*(x+3)*(x-2) | | 9x+36=100 | | 12+3m=7m-2m | | 8x+32=100 | | v+4=-12+1-v-1 | | 10=4-5n+4n | | 7x+28=100 | | 7x+21=100 | | 2x-3-6x=-7x-6 | | 7x+14=100 | | x-6=-14-x | | 3x+6x-10=53 | | x+8+2=4x+7 | | 6x+30=100 | | 6x+24=100 | | 6x+18=100 | | 6x+6=100 | | x-5=-5-7 | | -2d+3=-7 |

Equations solver categories